UCTD and SLE patients show increased levels of oxidative and DNA damage together with an altered kinetics of DSB repair. (24th September 2021) - Micheli, Consuelo; Parma, Alice; Tani, Chiara; Di Bello, Domenica; Falaschi, Aurora; Chiaramonte, Anna; Testi, Serena; Mosca, Marta; Scarpato, Roberto
Abstract: Immunological tolerance is a critical feature of the immune system; its loss might lead to an abnormal response of lymphocytes causing autoimmune diseases. One of the most important groups belonging to autoimmune disorders is the connective tissue diseases (CTD). CTD are classified among systemic rheumatic diseases and include pathologies such as systemic lupus erythematosus (SLE), and undifferentiated CTD (UCTD). In this study, we evaluated oxidative and genome damage in peripheral blood lymphocytes from patients with SLE and UCTD, further classified on the basis of disease activity and the presence/absence of a serological profile. Oxidative damage was evaluated in cell membrane using the fluorescent fatty acid analogue BODIPY 581/591 C11. The percentage of oxidised lymphocytes in both SLE and UCTD patients was higher than in the control group, and the oxidative stress correlated positively with both disease activity and autoantibody profile. The γH2AX focus assay was used to quantify the presence of spontaneous double strand breaks (DSBs), and to assess the abilities of DSBs repair system after T cells were treated with mitomycin C (MMC). Subjects with these autoimmune disorders showed a higher number of γH2AX foci than healthy controls, but no correlation with diseases activity and presence of serological profile was observed. In addition, patients displayed an altered response to MMC-induced DSBs, which led their peripheral cells to greatly increase apoptosis. Taken together our results confirmed an interplay among oxidative stress, DNA damage and impaired DNA repair, which are directly correlated to the aggressiveness and clinical progression of the diseases. We propose the evaluation of these molecular markers to better characterise SLE and UCTD, aiming to improve the treatment plan and the quality of the patients' life.